Chemo-and regioselective aqueous phase, co-acid free nitration of aromatics using traditional and nontraditional activation methods - Plasse, Kelsey M.; Mooney, Tara R.; Mastyugin, Maxim; Costa, Maximilian; Török, Béla (Frontiers in Chemistry, 2024)
Electrophilic aromatic nitrations are used for the preparation of a variety of synthetic products including dyes, agrochemicals, high energy materials, fine chemicals and pharmaceuticals. Traditional nitration methods use highly acidic and corrosive mixed acid systems which present a number of drawbacks. Aside from being hazardous and waste-producing, these methods also often result in poor yields, mostly due to low regioselectivity, and limited functional group tolerance. As a consequence, there is a need for effective and environmentally benign methods for electrophilic aromatic nitrations. In this work, the major aim was to develop reaction protocols that are more environmentally benign while also considering safety issues. The reactions were carried out in dilute aqueous nitric acid, and a broad range of experimental variables, such as acid concentration, temperature, time, and activation method, were investigated. Mesitylene and m-xylene were used as test substrates for the optimization. While the optimized reactions generally occurred at room temperature without any activation under additional solvent-free conditions, slight adjustments in acid concentration, stoichiometric equivalents, and volume were necessary for certain substrates, in addition to the activation. The substrate scope of the process was also investigated using both activated and deactivated aromatics. The concentration of the acid was lowered when possible to improve upon the safety of the process and avoid over-nitration. With some substrates we compared traditional and nontraditional activation methods such as ultrasound, microwave and high pressure, respectively, to achieve satisfactory yields and improve upon the greenness of the reaction while maintaining short reaction times.